Molecular markers for quantitative trait loci (QTLs) in maize gray leaf spot (GLS) resistance - Lehmensiek, Anke (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc.) -- University of Stellenbosch, 1998.